2022
DOI: 10.1080/20002297.2022.2096287
|View full text |Cite
|
Sign up to set email alerts
|

Breastmilk influences development and composition of the oral microbiome

Abstract: Background Human microbiomes assemble in an ordered, reproducible manner yet there is limited information about early colonisation and development of bacterial communities that constitute the oral microbiome. Aim The aim of this study was to determine the effect of exposure to breastmilk on assembly of the infant oral microbiome during the first 20 months of life. Methods The oral microbiomes of 39 infants, 13 who were never breastfed and 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Diversity and richness is strictly connected with taxonomy. Six main phyla were found: Firmicutes , Bacteroides , Proteobacteria , Actinobacteria , Fusobacteria , and Spirochaetes [ 7 , 9 , 17 , 33 , 34 , 43 ]. The valuable work of Arweiler et al [ 18 ] pointed out a huge β-diversity in microbial abundance between plaque and saliva samples, but this was not confirmed by Nomura et al [ 26 ], who found a similar biodiversity and richness between tongue and saliva samples.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Diversity and richness is strictly connected with taxonomy. Six main phyla were found: Firmicutes , Bacteroides , Proteobacteria , Actinobacteria , Fusobacteria , and Spirochaetes [ 7 , 9 , 17 , 33 , 34 , 43 ]. The valuable work of Arweiler et al [ 18 ] pointed out a huge β-diversity in microbial abundance between plaque and saliva samples, but this was not confirmed by Nomura et al [ 26 ], who found a similar biodiversity and richness between tongue and saliva samples.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial factor affecting the neonates’ microbiome development is represented by the type of nutrition. According to Butler et al [ 7 ], breastfed newborns present a greater abundance of healthy-associated oral bacteria, and maternal milk seems to play a prebiotic role. The introduction of solid food increases the oral microbiome heterogeneity in both breastfed and formula-fed infants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations